ETIOPATHOGENESIS OF HEMOLYTIC ANEMIA - Umida Rakhmatulloevna Narzulaeva; Xamrayeva Muxlisa Farmon qizi (Web of Journals Publishing, 2023)
Hemolytic anemias occur due to the predominance of erythrocyte destruction over formation. In hemolytic anemia, the life span of erythrocytes is reduced to 12-14 days and pathological hemolysis occurs.
Keywords: hemolysis, erythrocyte, membranopathies, enzymopathies, hemoglobinopathies, hemolytic jaundice.